Tesis doctoral: Spaces of consumption in the mobile metropolis: symbolic capital, multi-accessibility and spatial conditions for social interaction - Jose Carpio-Pinedo (Boletín de la Asociación de Geógrafos Españoles)
Carpio Pinedo, José. Spaces of consumption in the mobile metropolis: symbolic capital, multi-accessibility and spatial conditions for social interaction. Universidad Politécnica de Madrid (España), noviembre 2020. Directoras/es: Dr. Francisco Lamíquiz Daudén & Dr. Javier Gutiérrez Puebla.